Tectonics of kinetic architecture: Moving envelope, changing space and the shades of the shed - Akgün, Yenal; Erkarslan, Özlem Erdoğdu; Kavuncuoğlu, Canberk (Frontiers in Built Environment, 2022)
Buildings in our day are no more frozen pieces of music as ascribed by Johann Wolfgang von Goethe. They can move, rotate, flip and perform various physical gestures. This paper aims to explore the spatial, aesthetical, and technical characteristics of kinetic buildings within the framework of the theory of tectonics, which is still far away from covering the art form of movement. The study has been organized into two phases. The first phase sets up the theoretical framework of the topic by exploring the main dichotomy of the tectonic discourse on “ontological and representational parts of the building” and introduces the main concepts of kinetic architecture related to the characterization of architectural space. The second phase is a case study on The Shed as also known as Culture Shed in Hudson Yards in New York City. This part focuses on the interrelations between tectonics and the physical movement of architectural elements. The results indicate that the type of movement and the role of moving elements change not only the architectural space but also the tectonic character of the building. While some movements and moving parts are directly related to the representational aspects, some change the ontological character of the building. The impact of the movement on the tectonic character is a topic that hasn't been well investigated yet and has the potential to be developed through further research. As a result, the theoretical findings of this study can contribute to tectonic thinking during the design process of kinetic architectural products.